to find the radius you divide the circumference by 2pi
area is pi times radius to the 2nd power
So here we just are gonna distribute and simplify.
Answer:
x = 4/7
Step-by-step explanation:
x^3 = 64/ 343 // - 64/ 343
x^3 - ( 64/ 343 ) = 0
x^3 - 64 / 343 = 0
1*x^3 = 64/ 343 // : 1
x^3 = 64/ 343
x^3 = 64/ 343 // ^ 1/3
x = 4/ 7
That's a pretty confusing one. I think it's 10 minutes.
Answer and step-by-step explanation:
Break the bracket out would be the first step to evaluate this expression:
3(x-1)
= 3x - 3
Hope this helped :3